Ballistic performance of nanocrystalline and nanotwinned ultrafine crystal steel - Frontán, J; Zhang, Y; Dao, M; Lu, J; Gálvez, F; Jérusalem, A (2012)
Because of their remarkable mechanical properties, nanocrystalline metals have been the focus of much research in recent years. Refining their grain size to the nanometer range (<100 nm) effectively reduces their dislocation mobility, thus achieving very high yield strength and surface hardness - as predicted by the Hall-Petch relation - as well as higher strain-rate sensitivity. Recent works have additionally suggested that nanocrystalline metals exhibit an even higher compressive strength under shock loading. However, the increase in strength of these materials is generally accompanied by an important reduction in ductility. As an alternative, efforts have been focused on ultrafine crystals, i.e. polycrystals with a grain size in the range of 500 nm to 1 μm, in which "growth twins" (twins introduced inside the grain before deformation) act as barriers against dislocation movement, thus increasing the strength in a similar way as nanocrystals but without significant loss of ductility. Due to their outstanding mechanical properties, both nanocrystalline and nanotwinned ultrafine crystalline steels appear to be relevant candidates for ballistic protection. The aim of the present work is to compare their ballistic performance against coarse-grained steel, as well as to identify the effect of the hybridization with a carbon fiber-epoxy composite layer. Hybridization is proposed as a way to improve the nanocrystalline brittle properties in a similar way as is done with ceramics in other protection systems. The experimental campaign is finally complemented by numerical simulations to help identify some of the intrinsic deformation mechanisms not observable experimentally. As a conclusion, nanocrystalline and nanotwinned ultrafine crystals show a lower energy absorption than coarse-grained steel under ballistic loading, but under equal impact conditions with no penetration, deformation in the impact direction is smaller by nearly 40%. This a priori surprising difference in the energy absorption is rationalized by the more important local contribution of the deviatoric stress vs. volumetric stress under impact than under uniaxial deformation. Ultimately, the deformation advantage could be exploited in the future for personal protection systems where a small deformation under impact is of key importance. © 2011 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.